2022
DOI: 10.1039/d2re00137c
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature conversion of CO2 into quinazoline-2,4(1H,3H)-dione using deep eutectic solvents at atmospheric pressure with high efficiency

Abstract: High efficient and sustainable conversion of CO2 into quinazoline-2,4(1H,3H)-dione at room temperature and atmospheric pressure is challenging. Deep eutectic solvents (DESs) are considered as the green solvents of the 21st...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Mu and co-workers found that superbase-derived DESs could be volatilized after efficient capture CO 2 . Furthermore, Mu and co-workers found that DBN-based DESs could catalyze CO 2 into quinazoline-2,4­(1H,3H)-dione with the yield of >99% at room temperature and atmospheric pressure . Fu et al found that ethylene glycol-assisted DBU-based DESs could capture 0.163 w/w CO 2 at 40 °C and 1 atm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mu and co-workers found that superbase-derived DESs could be volatilized after efficient capture CO 2 . Furthermore, Mu and co-workers found that DBN-based DESs could catalyze CO 2 into quinazoline-2,4­(1H,3H)-dione with the yield of >99% at room temperature and atmospheric pressure . Fu et al found that ethylene glycol-assisted DBU-based DESs could capture 0.163 w/w CO 2 at 40 °C and 1 atm .…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, Mu and co-workers found that DBN-based DESs could catalyze CO 2 into quinazoline-2,4(1H,3H)-dione with the yield of >99% at room temperature and atmospheric pressure. 46 (NMR), and density functional theory calculation. 48 Xue and co-workers found that superbase-derived DESs containing DBN and pyridine N-oxide/2-picoline-N-oxide could dissolve cellulose with the solubility of 14.1 wt % 70 °C.…”
Section: Introductionmentioning
confidence: 99%
“…1 Additionally, CO 2 can also be regarded as a renewable C1 resource due to its inherent characteristics such as nontoxicity, low cost, abundant reserves, easy accessibility, etc. 2 Thus, various value-added chemicals and fuels including methanol, 3 hydrocarbons, 4 cyclic carbonates, 5 quinazolinediones, 6 amides 7 and others have been produced using CO 2 as a C1 feedstock, which offer green reaction routes for these organic syntheses from the viewpoint of green chemistry and sustainable development. However, since CO 2 is thermodynamically stable and kinetically inert, metal catalysts and harsh reaction conditions are generally required for its transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these chemicals, quinazoline-2,4(1 H ,3 H )-diones, regarded as pharmaceutical intermediates with a wide range of biological activity, have been successfully synthesized from CO 2 and o -aminobenzonitriles. This reaction is an atom-economical route, and it has been widely investigated using kinds of catalysts, such as metal oxides, [ 4 , 5 ] inorganic/organic supported/grafted catalysts, [ 6 , 7 , 8 , 9 ] organic bases, [ 10 , 11 , 12 , 13 , 14 , 15 ] water, [ 16 ] etc. However, most of these reaction systems have drawbacks, such as high CO 2 pressures, high temperatures, high catalyst loadings, long reaction times, and difficulties in recycling the catalysts.…”
Section: Introductionmentioning
confidence: 99%